INISIATIF MASYARAKAT UNTUK MENGHINDARI BANK HARIAN: MENGGALI PERSEPSI NEGATIF MASYARAKAT - M. Khanif Ardzani; Fitriyani Jauharotun Nafisah (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2025)
This study examines the community's initiative to avoid everyday banks, focusing on the growing negative perceptions among individuals regarding the operational practices of these financial institutions. Although everyday banks offer easy access to loans, many perceive high interest rates and unclear terms as creating significant financial risks. Using a qualitative approach, this study explores the experiences and perspectives of those involved in the "Stop Borrowing Money at Everyday Banks" movement. The results indicate that dissatisfaction with everyday banks' practices sparks social solidarity and collective initiatives to seek safer financing alternatives. Furthermore, the study finds that education and increased public awareness regarding rights and obligations in financial transactions are important factors in changing perceptions and behavior. Thus, this study provides insights into the importance of transparency and ethics in financial services and highlights the role of communities in driving positive change in the financial system. Keywords : Community Initiative, Daily Banking, Negative Perception.